Fertility Desire And Associated Factors Among HIV Positive Women Attending ART Clinics In Amhara Region Referral Hospitals In Northwest Ethiopia, 2017 - Mekonnen, Bilen (HIV AIDS (Auckl), 2019)
BACKGROUND: “Fertility desire” is the intention of people to have more children despite being diagnosed with HIV, whereas intentions denote a commitment to implement that desire. Despite the overwhelming effects of HIV on a fetus, there is a desire for fertility among people positive for the virus/disease worldwide.  Therefore, this study aimed to assess fertility desires and factors associated with sexually active HIV positive reproductive-age women attending ART clinics at Amhara region referral hospitals, Northwest Ethiopia. METHODS: An institution-based cross-sectional study was conducted on reproductive-age women attending the clinics at the hospitals. A total of 427 eligible women were systematically included in the study. A semi-structured questionnaire was used to collect data via interviewer-administered techniques. EpiInfo7 and STATA 14 software was used for data entry and analysis, respectively. The logistic regression analysis method was used to identify factors associated with fertility desire. Factors that had p-values of ≤0.05 were considered statistically significant. RESULTS: The findings indicated that 40.3% (95% CI; 35.7%, 45.0%) of the participants reported they had the desire to have children in the future. Variables such as women in the age group of 25–34 years (AOR= 2.80, 95% CI; 1.68, 4.68), participating with their sexual partner (AOR=3.52, 95% CI; 1.36, 9.13) and married women (AOR=2.32, 95% CI; 1.05, 5.10) had a positive association with the outcome variable, whereas having one or more live children (AOR=0.19, 95% CI; 0.09, 0.39) and having no formal education (AOR= 0.51, 95% CI; 0.29, 0.89) had a negative association with fertility desire. CONCLUSION: The proportion of sexually active HIV-positive women with desire for children was high among women visiting referral hospitals. Therefore, programmers and policymakers need to expand new PMTCT services throughout the region and consider the effects of these factors on HIV-positive women, as they develop interventions.